Virtual reality usage intention in an intradialysis exercise program: Predictive analysis through a structural equation model. - Moscoso-Aguayo, P.; Salazar-Concha, C.; Gomez-Conesa, A.; Segura-Orti, E. (Journal of Human Behavior in the Social Environment)
In recent years several exercise programs have begun to use technology, the most used has been virtual reality (VR). Technology-based programs must first be accepted by the population, since, if they do not see the need, the probability of rejection is high. Therefore, it is necessary to first evaluate the intention to use technology to ensure the effectiveness of the intervention. The study aimed to determine the predictive capacity of variables associated with theories of human behavior, on the intention to use VR in an intradialysis exercise program. A sample of 324 hemodialysis patients (F = 140; M = 184) from Chile, filled out a questionnaire. Before this, information was provided regarding VR and the exercise program. Structural equation modeling was used to analyze results through SmartPLS. Results showed that the dependent variable had a good amount of variance explained by the model. The latent variables that strongly influenced the intention to use were perceived enjoyment, perceived utility, and social influence. It can be predicted that users will intend to use VR to perform intradialysis exercises if they consider that it´s entertaining, useful, and validated by their peers.